AN ANALYSIS OF ENGLISH SLANG WORDS USED IN EMINEM’S RAP MUSIC - Rani Evadewi; Jufrizal Jufrizal (English Language and Literature, 2018)
Slang is the informal language which is used in a particular group of people especially used by teenagers in their activities to communicate each other. This research paper aimed to identify the characteristics of slang and the dominance slang used in Eminem songs. This research paper used Abadi’s (2009, p.17) theory about the characteristics of slang. This study used qualitative approach with descriptive method. The writer found that the total data of slangs in Eminem songs were 47 slangs. There were 13 data of creativity,27 data of flippant, 5 data of fresh, and 2 data of onomatopoeic. The most dominance slang used in Eminem songs is Flippant.